CUX1 stimulates APE1 enzymatic activity and increases the resistance of glioblastoma cells to the mono-alkylating agent temozolomide. Issue 4 (26th September 2017) - Kaur, Simran; Ramdzan, Zubaidah M; Guiot, Marie-Christine; Li, Li; Leduy, Lam; Ramotar, Dindial; Sabri, Siham; Abdulkarim, Bassam; Nepveu, Alain
Abstract: Background: Cut Like homeobox 1 ( CUX1 ), which encodes an auxiliary factor in base excision repair, resides on 7q22.1, the most frequently and highly amplified chromosomal region in glioblastomas. The resistance of glioblastoma cells to the mono-alkylating agent temozolomide is determined to some extent by the activity of apurinic/apyrimidinic endonuclease 1 (APE1). Methods: To monitor the effect of CUX1 and its CUT domains on APE1 activity, DNA repair assays were performed with purified proteins and cell extracts. CUX1 protein expression was analyzed by immunohistochemistry using a tumor microarray of 150 glioblastoma samples. The effect of CUX1 knockdown and overexpression on the resistance of glioblastoma cell lines to temozolomide was investigated. Results: We show that CUT domains stimulate APE1 activity. In agreement with these findings, CUX1 knockdown causes an increase in the number of abasic sites in genomic DNA and a decrease in APE1 activity as measured in cell extracts. Conversely, ectopic CUX1 expression increases APE1 activity and lowers the number of abasic sites. Having established that CUX1 is expressed at high levels in most glioblastomas, we next show that the resistance of glioblastoma cells to temozolomide and to a combined treatment of temozolomide and ionizing radiation is reduced following CUX1 knockdown, but increased by overexpression of CUX1 or a short protein containing only 2 CUT domains, which is active in DNA repair but devoid of transcriptional activity. Conclusion: These findings indicate that CUX1 expression level impacts on the response of glioblastoma cells to treatment and identifies the CUT domains as potential therapeutic targets.